2020
DOI: 10.33533/jpm.v14i2.2170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on the Outcomes of Basic Immunization in Health Facilities

Abstract: The purpose of this study was to determine the impact of Covid 19 on basic immunization coverage, oriented to the number of Covid 19 cases mapped in the red, yellow, and green. This research provides the advantage of making a policy to improve children's health during a pandemic, particularly in preventing diseases that can be anticipated by immunization, such as tuberculosis, diphtheria, hepatitis, tetanus, meningitis, polio, and measles. This research can also be used as a basic for immunization in health fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Another study conducted by Iswati (2020) to determine the impact of the Covid-19 pandemic on vaccination coverage which oriented to the number of COVID-19 cases mapped based on red, yellow, green zones in the East Java area showed that vaccination coverage in the red zone had decreased (95%). The results of this study indicated that there was no significant relationship between the zone of the COVID-19 case area and vaccination coverage (BCG, Hb0, Pentabio 1, Pentabio2, Pentabio3, Polio, and Measles) [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by Iswati (2020) to determine the impact of the Covid-19 pandemic on vaccination coverage which oriented to the number of COVID-19 cases mapped based on red, yellow, green zones in the East Java area showed that vaccination coverage in the red zone had decreased (95%). The results of this study indicated that there was no significant relationship between the zone of the COVID-19 case area and vaccination coverage (BCG, Hb0, Pentabio 1, Pentabio2, Pentabio3, Polio, and Measles) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they have different understanding and attitudes toward the COVID-19 pandemic. The understanding and attitudes formed can influence the actions/behavior of the community, in this case, parents and health workers, and their relationship with the provision of vaccination services for children [23]. To maintain the public's demand for vaccination services during the COVID-19 pandemic, promotional strategies should be primarily planned to provide accurate children's health information, respond to public concerns, increase community relations, and encourage sustainable use of vaccination services.…”
Section: Discussionmentioning
confidence: 99%
“…There have been 64% of 107 countries experiencing the disruption or the delay in implementing routine immunization services, and 60 countries have delayed the implementation of immunization campaigns, especially measles and polio. This is certainly risky for the PD3I Extraordinary Events (KLB) to occur [30]. Given the background of the decline of incomplete basic immunization coverage in Pekalongan Regency and many delayed immunization programs during the COVID-19 pandemic, this study aims to conduct a quick analysis with Rapid Card Check (RCC) to identify immunization coverage data and factors related to immunization coverage for babies in Pekalongan Regency.…”
Section: Introductionmentioning
confidence: 99%
“…Polio dan Campak) 11. Di masa pandemi Covid-19 para tenaga kesehatan tetap mensosialosasikan dan mengoptimalkan pelayanan imunisasi kepada para bayi.…”
unclassified